Kompleksitas Notaris dalam Penerapan Prinsip Mengenali Penguna Jasa - Fransisca, Lydia; Rahman, Eli (Program Studi Kenotariatan Fakultas Hukum Universitas Pelita Harapan, 2026)
Notary profession is inherently vulnerable to being exploited by clients seeking to conceal the proceeds of Money Laundering and the financing of Terrorism. Therefore, notaries are designated as reporting parties who are obligated to implement the Know Your Customer (KYC) Principle. This principle requires notaries to conduct identification, verification, and ongoing monitoring of their clients. This research is a normative legal study employing a descriptive approach. The method used to analyze the issues is normative approach. This study aims to analyze the complexity of the application of Know Your Customer principle by notaries and the legal protection for notaries as reporting parties in efforts to prevent money laundering crimes. Based on the findings, it is evident that notaries, as reporting parties, continue to encounter various obstacles in the application of the Know Your Customer principle. Furthermore, to prevent notaries from being misused as intermediaries for the commission of Money Laundering and Terrorism Financing crimes, it is necessary to strengthen notaries capacity through continuous education, enhanced regulatory guidelines, and the support of a more integrated data verification system in collaboration with relevant institutions and a shift from conventional identification methods toward a due-diligence mechanism that utilizes advanced technologies to address modes of operation involving artificial-intelligence–based manipulation, deepfake identity fraud, and crypto-mixer transactions. This transformation is essential to ensure that the notary’s obligations in preventing Money Laundering and Terrorist Financing can be carried out in a more coherent, effective, and compliant manner with the evolving Anti-Money Laundering and Counter-Terrorist Financing regime. Bahasa Indonesia Abstract: Notaris merupakan jabatan yang rentan untuk dimanfaatkan oleh pengguna jasa dalam upaya menyembunyikan hasil Tindak Pidana Pencucian Uang dan Tindak Pidana Pendanaan Terorisme. Oleh karena itu, notaris ditetapkan sebagai salah satu pihak pelapor yang berkewajiban menerapkan prinsip mengenali pengguna jasa. Prinsip ini mengharuskan notaris untuk melakukan identifikasi, verifikasi dan pemantauan terhadap pengguna jasanya. Penelitian ini adalah penelitian hukum normatif dengan tipe penelitian deskriptif. Pendekatan masalah yang digunakan adalah pendekatan normatif. Penelitian ini bertujuan untuk menganalisis kompleksitas penerapan prinsip mengenali pengguna jasa oleh notaris serta perlindungan hukum bagi notaris sebagai pihak pelapor dalam upaya pencegahan tindak pidana pencucian uang. Berdasarkan hasil penelitian ini, diketahui bahwa notaris sebagai pihak pelapor masih menghadapi sejumlah hambatan dalam penerapan prinsip mengenali pengguna jasa. Kemudian untuk mencegah keterlibatan notaris sebagai pihak yang rentan dimanfaatkan dalam Tindak Pidana Pencucian Uang dan Tindak Pidana Pendanaan Terorisme, maka perlu dilakukan penguatan kapasitas notaris melalui pendidikan berkelanjutan, peningkatan regulasi teknis, serta dukungan sistem verifikasi data yang lebih terintegrasi dengan lembaga-lembaga terkait dan perubahan pola identifikasi konvensional menuju mekanisme due diligence yang memanfaatkan teknologi mutakhir untuk menghadapi modus berbasis kecerdasan artifisial, Deepfake, dan crypto mixer sehingga kewajiban pencegahan TPPU/TPPT oleh notaris dapat terlaksana secara lebih sinkron, efektif, dan sejalan dengan perkembangan rezim Anti TPPU dan TPPT.